Make or buy analysis for cooked sausage products - Ausloos, Peter (Kansas State University, 2011)
Johnsonville Sausage is a privately held company based in Sheboygan Falls, WI. The company has a growing cooked sausage business and is evaluating options to expand capacity. Investing in either of two existing facilities or outsourcing production to a co-manufacturer is being considered in this make versus buy analysis. Intense competition in the category and uncertain raw material markets are considerations in the evaluation. Data used for the analyses were obtained from Johnsonville sources. Assumptions for the “make” analyses were based on existing data where applicable such as labor and utilities, and in other cases assumptions were made based on company knowledge of the process. Johnsonville engineers worked closely with equipment vendors to develop the building and equipment investment plan. Data for the “buy” alternative were received from a prequalified co-packer with advanced manufacturing technology. A Net Present Value (NPV) model is developed for each alternative and used to determine financial viability of each. The models consider varying investment requirements, freight rates and cost of goods for each alternative. Sensitivity analyses are performed to address key variables such as raw material prices and sales volume. The paper concludes that investment in Sheboygan is a viable option; however, the investment poses risk if raw material prices rise and or volume declines from expected projections. Therefore, the recommendation is to outsource production and initiate the Sheboygan project when the co-packed volume reaches 15 million pounds.
Keywords: Make vs buy; Net present value; Cooked sausage; Contract manufacturing